Leveraging geospatial data to evaluate women's employment opportunities in the renewable energy sector - Mayen Huerta, Carolina; Ivanescu, Clara; Herfort, Benjamin; Badowski, Piero; Gontariu, Dragos (Energy research & social science, 2025)
The Renewable Energy (RE) sector has grown significantly in response to the global climate crisis, yet women's participation remains disproportionately low, with many confined to lower-paid, non-technical roles. This persistent gender disparity could limit the sector's potential unless diversity is actively promoted. Traditional studies on women's employment in RE often overlook critical spatial factors, such as access to public transportation, safety, and neighborhood walkability, which are vital for understanding women's job access. To address these gaps, a Geospatial Women's Employment Analytical Framework (GeoWEAF) was developed, identifying 15 key spatial factors across three dimensions: Contextual, Accessibility, and Place-Characterization. These dimensions are crucial for evaluating whether an environment supports women's access to employment in the RE sector. The GeoWEAF was piloted in Saint Lucia to assess its practical application and effectiveness. It was designed as a decision-making tool for policymakers, offering data-driven insights that enable evidence-based decisions accounting for geographic disparities. By integrating spatial indicators into the evaluation of women's employment opportunities, the GeoWEAF provides a comprehensive understanding of the spatial dynamics shaping women's employment prospects, thereby facilitating targeted interventions to promote gender equity in the workforce.
Online veröffentlicht: 30. Dezember 2024
Gesehen am 12.06.2025